The influence of land cover variation on soil erosion vulnerability around coal mining concession areas in South Borneo - Supandi Supandi; Yudha Hardiyanto Eka Saputra; Yusanto Nugroho; Suyanto Suyanto; Gusti Syeransyah Rudy; Pandu Yudha Adi Putra Wirabuana (Brawijaya University, 2023)
The availability of information about soil erosion vulnerability is necessary as a primary consideration to determine the effort of soil conservation, particularly in the coal mining area. This study aimed to estimate the potential risk of soil erosion from land cover variation in a coal mining concession site in South Borneo. Data were taken from 18 stations of soil erosion monitoring which were evenly distributed in each land cover. Soil erosion vulnerability was quantified using the Universal Soil Loss Equation (USLE) method. The comparison mean of soil erosion among land cover types was evaluated using the Kruskal-Wallis test and followed by the Nemenyi test with a significant level of 5%. Results found that the potential risk of soil erosion was significantly different among land covers (p<0.05). The highest soil erosion vulnerability was noted in the reclamation area of 1,012.3 t ha-1 year-1, while the lowest risk of soil erosion was observed in plantation forests of 47.9 t ha-1 year-1. Surprisingly, the potential risk of soil erosion in natural forests was four times higher than in oil palm plantations. Besides being located in hilly areas with high slope levels, the vegetation density in natural forests was relatively low. However, our study recorded there were two critical factors that highly correlated to soil erosion vulnerability, i.e., soil erodibility (R = 0.89; p<0.05) and slope length and steepness (R = 0.85; p<0.05).